Femoral Geometry in Bisphosphonate-related Atypical Femoral Fracture and Bisphosphonate-naïve Atypical Femoral Fracture - Songsantiphap, Wachirawit; Therdyothin, Atiporn; Amphansap, Tanawat (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: To compare the radiographic characteristics of femoral geometry between bisphosphonate-related atypical femoral fracture (BPAFF) and bisphosphonate-naïve atypical femoral fracture (BPnAFF). Methods: A case-control study was conducted at the Police General hospital in Bangkok, Thailand, from January 2012 to December 2023; medical records and all available radiographs of hip and femoral fractures were reviewed. Atypical femoral fractures (AFF) were defined using the American Society for Bone and Mineral Research (ASBMR) 2013 criteria. BPAFF was identified in patients with a documented history of bisphosphonate prescription. The analysis encompassed a comparative assessment of femoral geometry parameters, including femoral offset, neck shaft angle, and lateral cortical thickness index (LCTi), between individuals with BPAFF and BPnAFF. Results: A total of 13 BPAFFs and 10 BPnAFFs were identified in 19 patients. The prevalence rate in our hospital was 1.69%. Patients with BPAFF were comparatively younger (73.46±6.30 vs. 82.6±3.71 years, p<0.001). Fractures were more prevalent in the subtrochanteric region in the BPAFF group (10 [76.92%] vs. 3 [30%], p=0.04). BPAFF group had significantly higher LCTi at both subtrochanteric region (0.258±0.050 vs 0.211±0.067, p=0.037), and the femoral shaft level (0.357±0.056 vs 0.288±0.059, p=0.005). However, no statistically significant differences were observed in other femoral geometry parameters between both groups. Conclusions: BPAFF exhibited a higher LCTi at the subtrochanteric and femoral shaft levels than BPnAFFs. On average, patients with BPAFF were younger than those with BPnAFF. Most BPAFF cases occurred in the subtrochanteric region, whereas BPnAFF cases were more commonly located in the diaphysis.